Organizational politics on employee performance: an exploratory study on readymade garments employees in Bangladesh - Rahman, Sabbir; Hussain, Bashir; Haque, A. K. M. Ahasanul (2011)
Purpose – The purpose of this paper is to study the impact of organizational politics on the performance of readymade garments employees in Bangladesh. The other purpose is to empirically test the hypothesized relationship of the research framework. This study also highlighted some propositions to guide future empirical research.